Regional Living and Community Participation: Are People with Disability at a Disadvantage? - McPhedran, S (My University, 2010)
There is considerable evidence that people with disability are at a heightened likelihood of experiencing disadvantage in many facets of life. A greater likelihood of disadvantage may in turn increase the risk of exclusion from a range of opportunities, including social participation. However, factors that may lead to ‘double disadvantage’ among people with disability—such as living outside major cities—have not been well assessed in Australia in relation to social connectedness. The current study compared various socioeconomic, life satisfaction, community participation and social support measures among prime working age regional people with and with no disability. People with disability experienced greater relative disadvantage and reported lower levels of perceived social support compared with people with no disability. Irrespective of disability status, men in regional Australia reported lower levels of social support than women. However, engagement in community activities such as volunteering did not differ as a function of disability status. This in turn suggests potential avenues for consideration in terms of strengthening social connectedness among regional people with disability, and addressing the risk of social exclusion for this group.
Australian Social Policy
Keywords: Health -- Disability; Location -- Regional; Health; Disadvantage; Location; Health and wellbeing; Housing, communities and neighbourhoods; Health; Location; Disadvantage; Regional; Disability; Housing, communities and neighbourhoods; Health and wellbeing